Strong Light‐Matter Coupling: Enhanced Delayed Fluorescence in Tetracene Crystals by Strong Light‐Matter Coupling (Adv. Funct. Mater. 36/2019). (3rd September 2019) - Berghuis, Anton Matthijs; Halpin, Alexei; Le‐Van, Quynh; Ramezani, Mohammad; Wang, Shaojun; Murai, Shunsuke; Gómez Rivas, Jaime
Abstract : Tetracene is an organic semiconductor that has the potential to enhance solar cell efficiency by singlet fission. In article number 1901317, Anton Matthijs Berghuis, Jaime Gómez Rivas, and co‐workers demonstrate the strong coupling of tetracene crystals to open plasmonic nanoparticle arrays. This coupling leads to hybridization of the singlet energy levels, and results in an enhanced delayed emission from tetracene (Artwork by ICMS Animation Studio, TU/e).